Cell‐surface signaling in Pseudomonas: stress responses, iron transport, and pathogenicity. Issue 4 (2nd July 2014) - Llamas, María A.; Imperi, Francesco; Visca, Paolo; Lamont, Iain L.
Abstract Membrane‐spanning signaling pathways enable bacteria to alter gene expression in response to extracytoplasmic stimuli. Many such pathways are cell‐surface signaling (CSS) systems, which are tripartite molecular devices that allow Gram‐negative bacteria to transduce an extracellular stimulus into a coordinated transcriptional response. Typically, CSS systems are composed of the following: (1) an outer membrane receptor, which senses the extracellular stimulus; (2) a cytoplasmic membrane‐spanning protein involved in signal transduction from the periplasm to the cytoplasm; and (3) an extracytoplasmic function (ECF) sigma factor that initiates expression of the stimulus‐responsive gene(s). Members of genus Pseudomonas provide a paradigmatic example of how CSS systems contribute to the global control of gene expression. Most CSS systems enable self‐regulated uptake of iron via endogenous (pyoverdine) or exogenous (xenosiderophores, heme, and citrate) carriers. Some are also implicated in virulence, biofilm formation, and cell–cell interactions. Incorporating insights from the well‐characterized alginate regulatory circuitry, this review will illustrate common themes and variations at the level of structural and functional properties of Pseudomonas CSS systems. Control of the expression and activity of ECF sigma factors are central to gene regulation via CSS, and the variety of intrinsic and extrinsic factors influencing these processes will be discussed.